2021
DOI: 10.22541/au.163451218.80057296/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The xylem of anisohydric Quercus alba L. is more vulnerable to embolism than isohydric co-dominants

Abstract: The coordination of plant leaf water potential (Ψ) regulation and xylem vulnerability to embolism is fundamental for understanding the tradeoffs between carbon uptake and risk of hydraulic damage. There is a general consensus that trees with vulnerable xylem regulate Ψ more conservatively than plants with resistant xylem. We evaluated if this paradigm applied to three important eastern US temperate tree species, Quercus alba L., Acer saccharum Marsh., and Liriodendron tulipifera L., by synthesizing 1600 Ψ obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…However, at a large scale, species in xeric climates need more negative Ψ close for carbon assimilation and more negative P50 for improving hydraulic safety, while a wider safety margin of xeric species also tends to be more isohydric, this stomatal strategy would be more successful under extreme drought conditions (Martin-StPaul et al, 2017;Pivovaroff et al, 2018). In addition, one recent local study also confirmed that anisohydric Quercus alba L. is more vulnerable to embolism than isohydric co-dominants (Benson et al, 2022). Overall, SSM provides a comprehensive isohydric-anisohydric framework to characterize plant response to drought.…”
Section: The Sequence Of Water Potentials For Physiological Dysfuncti...mentioning
confidence: 99%
“…However, at a large scale, species in xeric climates need more negative Ψ close for carbon assimilation and more negative P50 for improving hydraulic safety, while a wider safety margin of xeric species also tends to be more isohydric, this stomatal strategy would be more successful under extreme drought conditions (Martin-StPaul et al, 2017;Pivovaroff et al, 2018). In addition, one recent local study also confirmed that anisohydric Quercus alba L. is more vulnerable to embolism than isohydric co-dominants (Benson et al, 2022). Overall, SSM provides a comprehensive isohydric-anisohydric framework to characterize plant response to drought.…”
Section: The Sequence Of Water Potentials For Physiological Dysfuncti...mentioning
confidence: 99%